Bedaquiline: A New Hope for Shorter and Better Anti-Tuberculosis Regimens - Riccardi, Niccolò; Del Puente, Filippo; Magnè, Federica; Taramasso, Lucia; Di Biagio, Antonio (Recent Patents on Anti-Infective Drug Discovery, 2018)
Background: In 2014, an estimated 1.8 million people died from Mycobacterium tuberculosis (MTB); moreover, 680,000 people developed multidrug-resistant TB (MDRTB). Methods: Currently available anti-MDR and XDR regimens are long-lasting and expensive, need high adherence and are undermined by a high frequency of adverse drug events, thus leading to a low success rate; furthermore, in the last 50 years only two new molecules, bedaquiline (BDQ) and delamanid, have been approved and released for the treatment of MDR-TB. Results: BDQ, patent number US 7,498,343B2, is a diarylquinoline anti-mycobacterial drug, active regardless of the state of MTB; in fact, its efficacy is conserved against replicating and non-replicating bacilli, despite extracellular or intracellular location. BDQ has been approved by the Food and Drug Administration (FDA) only for combination treatment of pulmonary multidrug-resistant tuberculosis (MDR-TB), in adult patients, when an effective treatment cannot be provided otherwise due to resistance or poor tolerability; however, due to high bactericidal activity, BDQ may be used in future to treat extrapulmonary tuberculosis and Mycobacterium other than tuberculosis (MOTT) infection. Conclusion: BDQ may play a major role to get closer to TB eradication and to ensure higher retention in care, even in fully susceptible MTB strains and against non-replicating mycobacteria in latent-TB, providing an alternative to standard regimen.
Keywords: strains